"Ti Na Nyang" – "We Can" - International Center for Tropical Agriculture; Braslow, Juliet; Lolig, Victor; Florence, Anfaara; Snyder, Katherine A.; Dittoh, Saa; Atindana, Sandra (2016)
This participatory video titled “We Can” was filmed, produced, and directed by a group of 11 farmers and community members from Damolgo and Sekoti, Ghana. With this video they want to communicate the message: ‘we can use our combined knowledge to address the land management challenges we face.’ The film features farmers describing the importance of trees, stone bunds, contour planting and vetiver grass strips, mulching and manuring and the negative effects of bush burning. Through a 6 day process facilitated by CIAT and UDS, the farmers learned video techniques, interviewing skills, and developed the story they wanted to share with their community, local leaders, and the world.In English and Frafra.